Persepsi Nasabah Tentang Program Layanan Mobile UGT pada BMT UGT Nusantara Capem Labang dalam Meningkatkan Literasi Keuangan Digital di Kalangan Masyarakat - Inayatur Rohimah; Anizah Anizah; Mashudi Mashudi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
The development of digital technology has driven the transformation of financial services, including in Islamic microfinance institutions. One form of innovation is the implementation of mobile banking services, which aims to improve transaction efficiency and digital financial literacy among the public. This study aims to analyze customer perceptions of the Mobile UGT service program at BMT UGT Nusantara Labang Branch and its role in improving digital financial literacy among the public. This study uses a qualitative approach with a descriptive method. Data was collected through in-depth interviews, observations, and documentation of five active customers who have used the Mobile UGT service. The results show that customers generally have a positive perception of the Mobile UGT service. The application is considered easy to use, practical, and able to facilitate various financial transactions such as checking balances, transferring funds, and making payments, without having to come directly to the BMT office. In addition to increasing transaction efficiency, the use of Mobile UGT also contributes to improving customers' digital financial literacy, as reflected in their increased understanding of income and expenditure management, budget planning, utilization of digital transaction features, and awareness of data and account security. However, this study also found several obstacles, mainly related to technical disruptions to the application and internet network limitations. Overall, the Mobile UGT service plays an important role in supporting customers' financial independence and digital financial inclusion. This study recommends strengthening technological infrastructure and continuing education programs to optimize the benefits of digital financial services in the BMT environment.